A review of strategies to improve rational prescribing in asthma. (December 2014) - Inam, Shafqat; Lipworth, Wendy; Kerridge, Ian; Day, Richard
Abstract: Background: There are well‐recognised gaps between evidence‐based recommendations and prescribing practices in asthma. While different strategies have been devised to improve rational prescribing, the impact of these is uncertain. Aim: To examine the characteristics and effectiveness of strategies to improve rational prescribing in asthma. Method: We systematically searched electronic databases to find studies that reported on strategies to improve prescribing in asthma, or included rational prescribing as one of the main components of the program. Results: There were 13 relevant studies. All of the strategies described in these studies involved physician education using a variety of modalities; two of the trials also included patient‐specific prescribing direction; 12 of 13 studies reported improved prescribing practice. There was significant heterogeneity in the interventions and outcome criteria employed by the studies. Conclusion: Strategies to improve rational prescribing in asthma show promise, but the significant methodological heterogeneity, and the absence in most cases of demonstrable clinical benefit, raise concerns about their applicability in clinical practice.